2016
DOI: 10.1063/1.4941757
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermoelectric performance of Cu2Se/Bi0.4Sb1.6Te3 nanocomposites at elevated temperatures

Abstract: Bi2Te3-based thermoelectric materials with large thermoelectric figure of merit, ZT, at elevated temperatures are advantageous in power generation by using the low-grade waste heat. Here, we show that incorporation of small proportion (0.3 vol. %) of nanophase Cu2Se into BiSbTe matrix causes an enhanced high-temperature thermopower due to elevated energy filtering of carriers and inhibition of minority transport besides enhanced phonon blocking from scattering at interfaces, which concurrently result in an ∼20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 23 publications
1
23
0
1
Order By: Relevance
“…Dou et al fabricated Bi 0.4 Sb 1.6 Te 3 -based NCs embedded with amorphous SiO 2 nanoparticles and found that the enhancement of ZT was attributed to the increase in Seebeck coefficient and reduction in thermal conductivity [61]. Guo et al [62] fabricated Bi 0.4 Sb 1.6 Te 3 -based NCs incorporated with small proportion (0.3 vol%) of nanophase Cu 2 Se and found that ZT ≈ 1.6 could be obtained at 488 K. Fan et al [63] reported the TE transport in a p -type Bi 0.4 Sb 1.6 Te 3 -based NCs fabricated by a rapid and high throughput method of mixing nanoparticles obtained though melt spinning as shown in Figure 3. The electrical conductivity of 40 wt% NC in Figure 3a is reduced that is different from that in Figure 2a.…”
Section: Nanocomposites For Thermoelectricitymentioning
confidence: 99%
“…Dou et al fabricated Bi 0.4 Sb 1.6 Te 3 -based NCs embedded with amorphous SiO 2 nanoparticles and found that the enhancement of ZT was attributed to the increase in Seebeck coefficient and reduction in thermal conductivity [61]. Guo et al [62] fabricated Bi 0.4 Sb 1.6 Te 3 -based NCs incorporated with small proportion (0.3 vol%) of nanophase Cu 2 Se and found that ZT ≈ 1.6 could be obtained at 488 K. Fan et al [63] reported the TE transport in a p -type Bi 0.4 Sb 1.6 Te 3 -based NCs fabricated by a rapid and high throughput method of mixing nanoparticles obtained though melt spinning as shown in Figure 3. The electrical conductivity of 40 wt% NC in Figure 3a is reduced that is different from that in Figure 2a.…”
Section: Nanocomposites For Thermoelectricitymentioning
confidence: 99%
“…Other novel concepts include grain boundary engineering, [26,27] the formation of high entropy alloys [28] and design of nanocomposites. [29] The formation of composites based on hierarchical microstructures containing a primary matrix phase embedded with secondary-phase inclusions spanning spatial scales from the micrometer scale down to the nanoscale has also proven to be a generally effective route to optimize thermoelectrics. [30,31] Very recently, a large increase in performance for Cu 2 Se was reported by two groups, including our own, using a doping strategy based on incorporating secondary carbon phases such as carbon fiber, carbon graphite powder, black carbon or carbon nanotubes into the Cu 2 Se matrix.…”
Section: Introductionmentioning
confidence: 99%
“…β-Cu2Se reveals "Phonon-Liquid Electron-Crystal" (PLEC) behavior, leading to intrinsically ultralow κ and good electrical transport properties [37], and in turn high zT values (> 1.5) at ~ 800-1000 K [32,[38][39][40]. α-Cu2Se also shows low κ due to anharmonicity [41,42] and relatively good electrical transport properties compared with other TE materials at the same temperature [43][44][45][46]. Actually, a maximum zT of ~ 1.16 of α-Cu2Se at 305 K has been predicted by using Single parabolic band (SPB) model when the carrier concentration is reduced to 3×10 19 cm -3 [47], showing great potential to promote α-Cu2Se as a near-room-temperature TE material.…”
Section: Introductionmentioning
confidence: 99%